2013
DOI: 10.2337/dc12-1050
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Serum Concentrations of 25-Hydroxycholecalciferol Are Associated With Increased Risk of Progression to Impaired Fasting Glucose and Diabetes

Abstract: OBJECTIVETo study the association between vitamin D status and the risk of incident impaired fasting glucose (IFG) and diabetes in a population-based cohort of diabetes-free subjects.RESEARCH DESIGN AND METHODSIn a historical prospective cohort study of subjects from the Clalit Health Services database, which includes information on nearly 4 million people, diabetes-free subjects aged 40–70 years with serum 25-hydroxycholecalciferol (25-OHD) measurements available were followed for 2 years to assess the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 32 publications
4
33
0
1
Order By: Relevance
“…Our results are consistent with previous reports that depicted the fact that hypovitaminosis D in adults may influence the risk of developing diabetes and metabolic syndrome [18,19]. A previous study has shown that Vitamin D levels are positively correlated with insulin sensitivity and negatively correlated with HbA1c levels, indicating Vitamin D deficiency as a predisposing factor in the pathogenesis of diabetes mellitus and cardiovascular diseases [20].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are consistent with previous reports that depicted the fact that hypovitaminosis D in adults may influence the risk of developing diabetes and metabolic syndrome [18,19]. A previous study has shown that Vitamin D levels are positively correlated with insulin sensitivity and negatively correlated with HbA1c levels, indicating Vitamin D deficiency as a predisposing factor in the pathogenesis of diabetes mellitus and cardiovascular diseases [20].…”
Section: Discussionsupporting
confidence: 83%
“…But, this requires large prospective cohort study for evaluation • of prophylactic and therapeutic roles of Vitamin D and calcium in early phase of insulin resistance and T2DM [18].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…35 We noted a negative correlation between fasting blood glucose and vitamin D levels in our study. This is in corroboration with Tsur et al 36 Present results also highlight that neonates are at particularly high risk of vitamin D deficiency. However, these results are not unexpected.…”
Section: Discussionsupporting
confidence: 81%
“…In a longitudinal study of 17 year follow up period, 40 percent reduction in risk of developing type 2 diabetes was observed in men and women with 25(OH) D levels above 28 ng/mL at baseline [56]. Tsur et al [57], evaluated the association of development of impaired fasting glucose (IFG) and diabetes with serum 25 (OH) D level in 4 million non diabetic subjects aged 40-70 years for 2 years. The subjects were divided into 5 subgroups according to serum 25(OH) D subgroups (25, 25.1-37.5, 37.6-50, 50.1-75, and >75 nmol/ L).…”
Section: Insulin Sensitivitymentioning
confidence: 98%